2015
DOI: 10.1088/0031-9155/60/10/r211
|View full text |Cite
|
Sign up to set email alerts
|

Functional optical coherence tomography: principles and progress

Abstract: In the past decade, several functional extensions of optical coherence tomography (OCT) have emerged, and this review highlights key advances in instrumentation, theoretical analysis, signal processing and clinical application of these extensions. We review five principal extensions: Doppler OCT (DOCT), polarization-sensitive OCT (PS-OCT), optical coherence elastography (OCE), spectroscopic OCT (SOCT), and molecular imaging OCT. The former three have been further developed with studies in both ex vivo and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 104 publications
0
56
0
Order By: Relevance
“…Recent advances in OCT technology have led to the development of so-called functional-OCT technologies [99], including Doppler OCT for the assessment of retinal blood flow and polarisation OCT for the assessment of birefringent tissues, such as ganglion cell axon densities [106]. Improvements to the underlying OCT technology have led to the development of swept source (SS)-OCT [168], Adaptive Optics (AO)-OCT [126], and Frequency-Domain (FD)-OCT [128].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…Recent advances in OCT technology have led to the development of so-called functional-OCT technologies [99], including Doppler OCT for the assessment of retinal blood flow and polarisation OCT for the assessment of birefringent tissues, such as ganglion cell axon densities [106]. Improvements to the underlying OCT technology have led to the development of swept source (SS)-OCT [168], Adaptive Optics (AO)-OCT [126], and Frequency-Domain (FD)-OCT [128].…”
Section: Techniques For Monitoring Retinal Ganglion Cell Healthmentioning
confidence: 99%
“…However, the authors only used the suggested design for Doppler OCT and optical coherence angiography imaging. We refer interested readers to [33,34] for a more detailed discussion on each of these techniques. Nonetheless, a broader range of research questions can be addressed by combining SD-OCT imaging techniques with other modalities such as fluorescence microscopy or electrophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Since scattering and reflection is a result of refractive index changes, OCT is particularly sensitive to refractive index inhomogeneity in a material. Currently, the majority of OCT applications are in biomedical imaging of the eye and other biological tissues such as the skin [4,5]. Since 2004, OCT has been successfully applied to a variety of cultural heritage [6][7][8][9] [19] and corrosion layer in metal-based artefacts [20].…”
Section: Introductionmentioning
confidence: 99%